1990
DOI: 10.1088/0029-5515/30/5/016
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic analysis of compound sawteeth on the Tokamak de Varennes

Abstract: A compound saawtooth consists of a subordinate relaxation followed by a main relaxation; it has approximately twice the period and the amplitude of a normal sawtooth. High resolution 2-D images, produced by the soft X-ray tomography system of the Tokamak de Varennes, are used to compare the different types of sawtooth relaxations. It appears that a reconnection process is involved for all collapses, although the reconnection is incomplete during the partial relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…This is consistent with the flattening process of the pressure profile (current profile) in the full reconnection model. These processes are illustrated in frames [8][9][10][11]. As the heat is removed from the core, the closed field line topology is established and recovers the poloidal symmetry as shown in frame 12.…”
Section: C) 2-d Images Of the Sawtooth Crash At High Field Sidementioning
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the flattening process of the pressure profile (current profile) in the full reconnection model. These processes are illustrated in frames [8][9][10][11]. As the heat is removed from the core, the closed field line topology is established and recovers the poloidal symmetry as shown in frame 12.…”
Section: C) 2-d Images Of the Sawtooth Crash At High Field Sidementioning
confidence: 93%
“…As a result, the hot spot deforms into a crescent shape and cooler plasmas are convectively induced into the concave section of the crescent hot spot without any reconnection process. This model was supported by x-ray tomography [10] on the Joint European Tokamak (JET) device; however, a later experimental study [11] on the Tokamak de Varennas (TdeV) device concluded that there exists no unique solution for the image through the inversion process of the chordal measurements of the x-ray tomography when only a limited number of independent viewing lines are used.…”
Section: Background Of the Physics Of The Sawtooth Oscillationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the hot spot deforms into a crescent shape, the cooler outside portion of the plasma is convectively inducted into the core region, resulting in a flattening of the core pressure profile. This model was experimentally supported by x-ray tomography [12] on the Joint European Tokamak; however, a later experimental study [13] on the Tokamak de Varrenes concluded that the tomographic reconstruction is ill-posed and that there is no unique solution for the image through the inversion process of a limited number of chordal measurements from only a few independent views. The distinctively different evolution of the hot spot and/or cold island formation between the quasi-interchange model and full reconnection model could not be conclusively identified due to the lack of reliable 2D experimental tools.…”
mentioning
confidence: 98%
“…Another theoretical model is the 'quasi-interchange' model [8] where the cooler plasma convectively flows into the plasma core and the hot spot evolves into a crescent shape due to the magnetic shear of the m/n/=1/1 mode without any magnetic reconnection process. Experimental verification of such a distinctively different evolution of the hot spot /island between the full reconnection model and the quasi-interchange model has not been conclusive due to the lack of accurate 2-D experimental tools [9]. However, in current density profile measurements [10,11], only slight changes of current density were observed while the reconnection time was much faster than expected on theoretical grounds.…”
Section: High Resolution (Temporal and Spatial) Two Dimensional Imagmentioning
confidence: 97%